Caveolin-1 Regulates Perivascular Aquaporin-4 Expression After Cerebral Ischemia - Filchenko, Irina; Blochet, Camille; Buscemi, Lara; Price, Melanie; Badaut, Jerome; Hirt, Lorenz (Frontiers in Cell and Developmental Biology, 2020)
Edema is a hallmark of many brain disorders including stroke. During vasogenic edema, blood-brain barrier (BBB) permeability increases, contributing to the entry of plasma proteins followed by water. Caveolae and caveolin-1 (Cav-1) are involved in these BBB permeability changes. The expression of the aquaporin-4 (AQP4) water channel relates to brain swelling, however, its regulation is poorly understood. Here we tested whether Cav-1 regulates AQP4 expression in the perivascular region after brain ischemia in mice. We showed that Cav-1 knockout mice had enhanced hemispheric swelling and decreased perivascular AQP4 expression in perilesional and contralateral cortical regions compared to wild-type. Glial fibrillary acidic protein-positive astrocytes displayed less branching and ramification in Cav-1 knockout mice compared to wild-type animals. There was a positive correlation between the area of perivascular AQP4-immunolabelling and branch length of Glial fibrillary acidic protein-positive astrocytes in wild-type mice, not seen in Cav-1 knockout mice. In summary, we show for the first time that loss of Cav-1 results in decreased AQP4 expression and impaired perivascular AQP4 covering after cerebral ischemia associated with altered reactive astrocyte morphology and enhanced brain swelling. Therapeutic approaches targeting Cav-1 may provide new opportunities for improving stroke outcome. Significance Statement Severe brain edema worsens outcome in stroke patients. Available treatments for stroke-related edema are not efficient and molecular and cellular mechanisms are poorly understood. Cellular water channels, aquaporins (AQPs), are mainly expressed in astrocytes in the brain and play a key role in water movements and cerebral edema, while endothelial caveolins have been suggested to play a role in vasogenic edema. Here we used an integrative approach to study possible interaction between AQP4 and caveolin-1 (Cav-1) after stroke. Absence of Cav-1 was associated with perivascular changes in AQP4 expression and enhanced brain swelling at 3 days after cerebral ischemia. The present work indicates a direct or indirect effect of Cav-1 on perivascular AQP4, which may lead to novel edema therapy.